OBSERVATIONS ON THE OIL SARDINE FISHERY AT AYIROMTHENGU (ALLEPPEY DISTRICT) - Nair, G Sivankutty (Indian Journal of Fisheries, 2011)
The data regiirding oil sardine landings at Ayiromthengu during 1958 and 1959show tliat the fishery in this locality follows a definite cyclical change in the compositionof the catches. The maximum landings were recorded in March or April and the minimumin January. Juvenile sardines with a dominant size of 13 and 14 cm contributedto the bulk of the catches during both the years. Studies on the length frequency distributionshow that oil sardine attains the lengths of 10.0-10.5 cm, 16.0-16.5 cmand 18.0-IS.Scmat tbeageofflrst.secondandthirdyearsrespectively. The finding is corroboratedwith the growth checks on the preopercular bone.